An introduction to cable roof structures - Buchholdt, H. A. 1925- (Thomas Telford, 1999)
The second edition of this book provides structural engineers with a concise introduction to the architectural, structural and technological aspects of cable roofs, and supplies sufficient information for engineers to carry out their own designs. The improved methods for generating wind and earthquake histories have been included.
Previous ed. published: Cambridge: Press Syndicate of Cambridge 1985.
Keywords: Cable structures -- Design and construction.; elektronické knihy; electronic books